PENGARUH SOLVABILITAS, FINANCIAL DISTRESS DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Sektor Property & Real Estate Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Viany, Diva Octa; Sari, Ika (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Audit delay occurs when the date of submission of the financial statements and the date of completion of the audit have a time difference of more than 90 days after the closing statement. Audit Delay or audit delay occurs due to obstacles or errors during the audit process. Research was conducted to examine the effect of solvency, Financial Distress and company size on Audit Delay. The research population is property & real estate sector companies listed on the Indonesia Stock Exchange (IDX) 2020-2023. Applying Purposive Sampling as a sample collection technique with a total sample size of 208 sample data. This study, using secondary data and multiple linear regression analysis methods. Based on the research results obtained that, solvency has a positive effect on Audit Delay, Financial Distress has a negative effect on Audit Delay and company size has a negative effect on Audit Delay. in the results of this study also produce solvency, Financial Distress and company size have a simultaneous or joint influence on Audit Delay.